New Tendencies in the Development of Modern English - Alexandrova, Olga (Armenian Folia Anglistika, 2005)
The 21st century is facing a new qualitative level of technological advances which have had a significant impact on human lifestyle and human language alike. Since language is a most important means of cognition, it plays an essential role in the development process of the world. In this regard, English, being the most widely used language in the international communication, is, perhaps, the most flexible one. Under the external factors and due to ever-changing human thinking, language undergoes significant changes both in oral and in written speech as well as in the overall language system.